Employee choices for participating in corporate entrepreneurship in South Africa - Nikolov, Kristo Nikolov (My University, 2014)
Corporate entrepreneurship is identified as a means of achieving and sustaining long term company competitive advantage. Furthermore, academic literature suggests that corporate entrepreneurship leads to superior or increased company performance. In order to launch and implement corporate entrepreneurship ventures, employers require the participation of skilled, determined and passionate employees. To improve the understanding and further strengthen the theoretical foundations of corporate entrepreneurship incentive design, a conjoint choice analysis was modified and utilised, based on existing academic literature. A survey was carried out on 167 South African corporate employees, examining the effects of risk, reward, exerted effort and perceived probability of venture success as factors that influence employees’ willingness of participation in corporate entrepreneurship ventures. Using regression techniques, conjoint part-worth utilities were calculated, thus determining the effect of these factors. Furthermore, employee demographical characteristics were examined in order to determine whether employees’ gender, past entrepreneurial experience and years’ of work experience have an effect on the venture participation decision. The evidence from the study showed a significant relationship between the factors investigated and the employees’ decision to participate in a corporate venture. Moreover, employees’ past entrepreneurial experience and years of work experience were found to have an effect in the way that different employees perceive various factors pertaining to the participation decision.
MBA thesis
Keywords: Entrepreneurship; Corporate entrepreneurship